Dietary diversity and its associations with sleep quality and chronotype in young and middle-aged adults - Zhao, Anda; Chen, Yiting; Li, Zhen; Fan, Qing; Wu, Jiang (Frontiers in Nutrition, 2026)
BackgroundWhile sleep quality and chronotype are critical to wellbeing, the role of dietary diversity remains scarcely investigated, particularly among young and middle-aged adults. This study aimed to examine the associations of dietary diversity with sleep quality and chronotype, and to explore whether depression mediates these relationships.MethodsData were derived from the 2024–2025 China Nutrition and Sleep Survey (CNSS), including 4,128 adults aged 20–59 years. Dietary diversity indices, including total dietary diversity scores (DDS), plant-based DDS, animal-based DDS, anti-inflammatory diet diversity index (AIDDI) and protein-enriched diet diversity index (PEDDI), were calculated from food frequency questionnaires. Sleep quality, chronotype, and depression were assessed using the Pittsburgh Sleep Quality Index (PSQI), the Morningness-Eveningness Questionnaire-5 (MEQ-5), and the Patient Health Questionnaire-9 (PHQ-9), respectively. Linear and logistic regression analyses were performed, with propensity score matching (PSM) applied to reduce confounding. Mediation and interaction analyses were further conducted.ResultsHigher dietary diversity indices were significantly associated with lower PSQI scores and higher MEQ-5 scores, both before and after PSM. Depression might be partially involved in the observed associations with sleep quality and chronotype. The associations between dietary diversity and sleep quality were stronger among females, older adults, non-drinkers, and those with regular exercise or depressive symptoms, whereas associations with chronotype were generally consistent across subgroups.ConclusionsGreater dietary diversity is associated with better sleep quality and earlier chronotype, with depressive symptoms potentially playing a role in explaining these associations.